Analysis on Out-of-Plane Stability of Large-span Single Space Tube Truss during Hoisting. Issue 1 (February 2021) - Chen, S H; Yin, T Y; Sang, X X; Ye, B R; Ding, M
Abstract: In order to study the out-of-plane stability of the large-span single space tube truss during lifting, the eigenvalue buckling mode of the truss was calculated by mode analysis in ANSYS, the eigenvalue buckling mode with different combination coefficients was applied to the truss, and the stability bearing capacity was taken as the measurement to conduct the whole process tracking analysis. Finally, the most appropriate eigenvalue buckling mode combination was found as the initial imperfection, and it was applied to a large-span single regular triangle space tube truss and inverted triangle space tube truss to verify its stability during hoisting, respectively. The results show that the combination form of the eigenvalue buckling mode is the most appropriate initial imperfection. When the large-span single regular triangle space tube truss and inverted triangle space tube truss are hoisted, local buckling occurs when the body force is up to 0.30 times and 0.15 times of gravity, respectively, and overall instability occurs when the body force is up to 0.56 times and 0.51 times of gravity, respectively. It can be obviously obtained that the large-span single space tube truss may be destabilized under its own weight during hoisting, local buckling has occurred in some member bars before overall instability, and it is necessary to check the truss stability before hoisting in actual engineering.